Characterization and Analysis of Gas-Solid Flow Dynamics in Fluidized Bed Systems - de Araújo, Elaine M.G.; Barros, Emerson; Barros, António A.C. (Journal of Chemical Engineering Research Updates, 2024)
Fluidization is a critical process in various industrial applications, particularly in the oil and gas sector, where it plays a pivotal role in optimizing production, phase separation, and the efficiency of mass and heat transfer, as well as chemical reactions involved in physical and chemical operations. The significance of fluidization stems from its direct impact on key parameters such as pressure drop, flow velocity, particle concentration, and void fraction in multiphase flows. In this context, fluidization enhances the interaction between fluid and solid particles, reducing resistance to heat and mass transfer and promoting material homogenization. This experimental study aims to investigate the flow behavior of a particulate system within a fluidized bed, specifically focusing on the fraction of the continuous (gas) phase relative to a defined volume of solid particles. The results obtained, when compared to existing literature primarily concerned with the effects of particle size and flow rate on fluidization, demonstrate consistency in both qualitative and quantitative analyses. These findings suggest that the increase in the volume of the continuous phase in such flows is strongly influenced by the Reynolds number and the particle size within the system. Thus, this study makes significant contributions to the optimization of fluidization processes, particularly in industrial sectors like oil and gas. By providing detailed experimental insights into the factors that influence fluidized bed performance, the findings offer practical implications for improving the efficiency of heat and mass transfer, phase separation, and reaction rates in industrial applications where the behavior of the continuous phase is crucial.